Pó de rocha granítica na remoção de corante em efluente e aplicação em matriz de cimento Portland - Hawerroth, Mariane (2023)
This study aimed to evaluate the performance of granitic rock powder (PRG) in the removal of Basazol Yellow 5G dye through experimental tests with subsequent study of the post-adsorption granitic rock powder (PRGA) reactivity in Portland cement matrix. For this, the PRG was characterized by analyzing the surface area (BET) and the point of zero charge (pHpcz). Fourier Transform Infrared Spectrometry (FTIR), Scanning Electron Microscopy (SEM) analyzes were also carried out with the adsorbent material before and after adsorption. The adsorption tests in synthetic effluent were conducted in batches, in which the operational conditions of granulometry, temperature and pH were evaluated, in addition to the analysis of kinetic, equilibrium, thermodynamic parameters and desorption capacity. Considering the operational conditions defined for the synthetic effluent, the industrial effluent studied was submitted to tertiary treatments, adsorption, electrocoagulation and series processes to evaluate the removal of color, BOD and COD. Regarding the Portland cement matrix study, the PRGA was characterized by analysis of specific mass, moisture content, loss on ignition and X-ray fluorescence (FRX). To verify the pozzolanicity of the material, X-ray diffraction tests (DRX), modified Chapelle, pozzolanic activity index with lime (IAP) and performance index with cement (ID) were carried out. For the study with cement paste, tests were carried out on compressive strength, tensile strength by diametral compression, specific mass, voids index and water absorption by immersion. The operating conditions were defined as pH 7, 25 ºC and 200 mesh passing granulometry. The kinetic test indicated an equilibrium time of 240, 105, 60 and 40 minutes for temperatures of 25, 30, 40 and 50ºC, respectively. The pseudo-second order model was the one that best fitted the experimental data and the activation energy (71.35 kJ mol-1) showed the occurrence of chemosorption. Equilibrium data were best described by the Langmuir model, indicating that adsorption probably occurs in a monolayer. The process was evaluated as spontaneous, endothermic and with a decrease in disorder at the solid/liquid interface, in addition to presenting a low rate of dye desorption. The test in industrial effluent showed a better performance of color removal (72.95%), BOD (65.16%) and COD (20.71%) for the serial process. FRX analysis showed that PRG and PRGA are mostly composed of silicon oxide and aluminum oxide. The FRX analysis indicated the absence of amorphous halo in the samples and the presence of SiO2, albite and microcline. As for reactivity, PRG and PRGA did not meet the minimum requirements in the modified Chapelle test and resistance in the IAP and ID tests to classify them as pozzolanic materials. In the study of the filler effect with cement pastes, there was a favorable result for partial replacement of cement in mortars using both materials, with better performance with a 10% replacement. Based on the context of the circular economy, granitic rock powder showed potential for use in the treatment of effluent with the dye Basazol Yellow 5G and subsequent use as a filler in Portland cement matrix.